Kommunikativa orienteringar i kunskapsbyggande interaktion - Robert Walldén (Educare)
Exploring spoken interaction in the teaching of texts and content knowledge to linguistically diverse Grade 6 students, this article responds to the need of a more nuanced understanding of how different patterns of interaction function in knowledge-building classroom practices. The study is based on observations and transcriptions of recorded classroom interaction in different school subjects. The analysis is based on theoretical frameworks of communicative approaches, knowledge domains and discursive mobility. The result shows how patterns of classroom interaction are connected to important functions, such as building up prior knowledge, reminding students of key disciplinary concepts, reinforcing meanings in disciplinary texts, problematizing different aspects of how subject content is represented and enabling the diverse students to connect the subject content to personal experiences and process it with innovative use of the target language. The result also shows that movements towards a disciplinary discourse can be promoted by grounding the interaction in written texts and hindered by less functional use of everyday language.